Nanoscaled alloy formation from self-assembled elemental Co nanoparticles on top of Pt films - Han, Luyang; Wiedwald, Ulf; Biskupek, Johannes; Fauth, Kai; Kaiser, Ute; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2011)
The thermally activated formation of nanoscale CoPt alloys was investigated, after deposition of self-assembled Co nanoparticles on textured Pt(111) and epitaxial Pt(100) films on MgO(100) and SrTiO3(100) substrates, respectively. For this purpose, metallic Co nanoparticles (diameter 7 nm) were prepared with a spacing of 100 nm by deposition of precursor-loaded reverse micelles, subsequent plasma etching and reduction on flat Pt surfaces. The samples were then annealed at successively higher temperatures under a H2 atmosphere, and the resulting variations of their structure, morphology and magnetic properties were characterized. We observed pronounced differences in the diffusion and alloying of Co nanoparticles on Pt films with different orientations and microstructures. On textured Pt(111) films exhibiting grain sizes (20–30 nm) smaller than the particle spacing (100 nm), the formation of local nanoalloys at the surface is strongly suppressed and Co incorporation into the film via grain boundaries is favoured. In contrast, due to the absence of grain boundaries on high quality epitaxial Pt(100) films with micron-sized grains, local alloying at the film surface was established. Signatures of alloy formation were evident from magnetic investigations. Upon annealing to temperatures up to 380 °C, we found an increase both of the coercive field and of the Co orbital magnetic moment, indicating the formation of a CoPt phase with strongly increased magnetic anisotropy compared to pure Co. At higher temperatures, however, the Co atoms diffuse into a nearby surface region where Pt-rich compounds are formed, as shown by element-specific microscopy.
Keywords: alloy; Co; CoPt; epitaxy; HRTEM; magnetometry; nanoparticles; Pt; XMCD

Nanoparticles - Schmid, G. (Wiley-VCH, 2004)

Nanomaterials and Nanochemistry - Brèchignac, C.; Houdy, Ph.; Lahmani, M. (Springer, 2007)

(untitled) - Lu, A.-H.; Salabas, E. L.; Schüth, F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Goesmann, H.; Feldmann, C. (Angew. Chem., Int. Ed., 2010)

Nanotechnology: An Introduction to Nanostructuring Techniques - Köhler, M.; Fritzsche, W. (Wiley-VCH, 2007)

(untitled) - Kästle, G.; Boyen, H.-G.; Weigl, F.; Lengl, G.; Herzog, T.; Ziemann, P.; Riethmüller, S.; Mayer, O.; Hartmann, C.; Spatz, J. P.; Möller, M.; Ozawa, M.; et al. (Adv. Funct. Mater., 2003)

(untitled) - Krishnamoorthy, S.; Hinderling, C.; Heinzelmann, H. (Mater. Today, 2006)

(untitled) - Shevchenko, E. V.; Talapin, D. V.; Rogach, A. L.; Kornowski, A.; Haase, M.; Weller, H. (J. Am. Chem. Soc., 2002)

(untitled) - Sun, S.; Murray, C. B.; Weller, D.; Folks, L.; Moser, A. (Science, 2000)

(untitled) - Ethirajan, A.; Wiedwald, U.; Boyen, H.-G.; Kern, B.; Han, L.; Klimmer, A.; Weigl, F.; Kästle, G.; Ziemann, P.; Fauth, K.; Cai, J.; Behm, R. J.; et al. (Adv. Mater., 2007)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Honolka, J.; Lee, T. Y.; Kuhnke, K.; Enders, A.; Skomski, R.; Bornemann, S.; Mankovsky, S.; Minar, J.; Staunton, J.; Ebert, H.; Hessler, M.; Fauth, K.; et al. (Phys. Rev. Lett., 2009)

(untitled) - Li, Y.; Somorjai, G. A. (Nano Lett., 2010)

(untitled) - Chen, Y. J.; Hwang, E. J.; Shem, C. S. (J. Appl. Phys., 2008)

(untitled) - Bruno, P. (Phys. Rev. B, 1989)

(untitled) - Grange, W.; Galanakis, I.; Alouani, M.; Maret, M.; Kappler, J.-P.; Rogalev, A. (Phys. Rev. B, 2000)

(untitled) - Grange, W.; Maret, M.; Kappler, J.-P.; Vogel, J.; Fontaine, A.; Pétroff, F.; Krill, G.; Rogalev, A.; Goulon, J.; Finazzi, M.; Brookes, N. B. (Phys. Rev. B, 1998)

(untitled) - McIntyre, P. C.; Maggiore, C. J.; Nastasi, M. (Acta Mater., 1997)

(untitled) - Xu, X. M.; Liu, J.; Yuan, Z.; Weaver, J.; Chen, C. L.; Li, Y. R.; Gao, H.; Shi, N. (Appl. Phys. Lett., 2008)

(untitled) - Balestrino, G.; Martellucci, S.; Medaglia, P. G.; Paoletti, A.; Tebano, A.; Tucciarone, A. (Microsyst. Technol., 1999)

(untitled) - Scavia, G.; Agostinelli, E.; Laureti, S.; Varvaro, G.; Paci, B.; Generosi, A.; Rossi Albertini, V.; Kaciulis, S.; Mezzi, A. (J. Phys. Chem. B, 2006)

(untitled) - Krieger, M.; Plettl, A.; Steiner, R.; Boyen, H.-G.; Ziemann, P. (Appl. Phys. A, 2004)

(untitled) - Trautvetter, M.; Wiedwald, U.; Paul, H.; Minkow, A.; Ziemann, P. (Appl. Phys. A, 2011)

(untitled) - Bansmann, J.; Kielbassa, S.; Hoster, H.; Weigl, F.; Boyen, H. G.; Wiedwald, U.; Ziemann, P.; Behm, R. J. (Langmuir, 2007)

(untitled) - Boyen, H.-G.; Kästle, G.; Zürn, K.; Herzog, T.; Weigl, F.; Ziemann, P.; Mayer, O.; Jerome, C.; Spatz, J. P.; Möller, M.; Garnier, M. G.; Oelhafen, P. (Adv. Funct. Mater., 2003)

(untitled) - Kleibert, A.; Bulut, F.; Gebhardt, R. K.; Rosellen, W.; Sudfeld, D.; Passig, J.; Bansmann, J.; Meiwes-Broer, K. H.; Getzlaff, M. (J. Phys.: Condens. Matter, 2008)

(untitled) - Gries, W. H. (Surf. Interface Anal., 1996)

(untitled) - Chen, C. T.; Idzerda, Y. U.; Lin, H.-J.; Smith, N. V.; Meigs, G.; Chaban, E.; Ho, G. H.; Pellegrin, E.; Sette, F. (Phys. Rev. Lett., 1995)

(untitled) - Fauth, K. (Appl. Phys. Lett., 2004)

(untitled) - Goering, E.; Fuss, A.; Weber, W.; Will, J.; Schütz, G. (J. Appl. Phys., 2000)

(untitled) - Galanakis, I.; Alouani, M.; Dreyssé, H. (J. Magn. Magn. Mater., 2002)

(untitled) - O’Brien, W. L.; Tonner, B. P. (Phys. Rev. B, 1994)

(untitled) - Gambardella, P.; Rusponi, S.; Veronese, M.; Dhesi, S. S.; Grazioli, C.; Dallmeyer, A.; Cabria, I.; Zeller, R.; Dederichs, P. H.; Kern, K.; Carbone, C.; Brune, H. (Science, 2003)

(untitled) - Zeper, W. B.; van Kesteren, H. W.; Jacobs, B. A. J.; Spruit, J. H. M.; Garcia, P. F. (J. Appl. Phys., 1991)

(untitled) - Pan, M.; He, K.; Zhang, L.; Jia, J.; Xue, Q.; Kim, W.; Qiu, Z. Q. (J. Vac. Sci. Technol., A, 2005)

(untitled) - Ferrer, S.; Alvarez, J.; Lundgren, E.; Torrelles, X.; Fajardo, P.; Boscherini, F. (Phys. Rev. B, 1997)

(untitled) - Shapiro, A. L.; Rooney, P. W.; Tran, M. Q.; Hellman, F.; Ring, K. M.; Kavanagh, K. L.; Rellinghaus, B.; Weller, D. (Phys. Rev. B, 1999)

(untitled) - Boeglin, C.; Carriere, B.; Deville, J. P.; Heackmann, O.; Leroux, C.; Panissod, P. (Surf. Sci., 1989)

(untitled) - Wiedwald, U.; Fauth, K.; Heßler, M.; Boyen, H.-G.; Weigl, F.; Hilgendorff, M.; Giersig, M.; Schütz, G.; Ziemann, P.; Farle, M. (ChemPhysChem, 2005)

(untitled) - Marzke, R. F.; Glaunsinger, W. S.; Bayard, M. (Solid State Commun., 1976)

(untitled) - Garcia-Otero, J.; Porto, M.; Rivas, J. (J. Appl. Phys., 2000)

(untitled) - Harrell, J. W.; Wang, S.; Nikles, D. E.; Chen, M. (Appl. Phys. Lett., 2001)

(untitled) - Henkel, O. (Phys. Status Solidi, 1964)